Type I/II Interferon in HIV-1-Infected Patients: Expression in Gut Mucosa and in Peripheral Blood Mononuclear Cells and Its Modification upon Probiotic Supplementation - Claudia Pinacchio; Giuseppe Corano Scheri; Maura Statzu; Letizia Santinelli; Giancarlo Ceccarelli; Giuseppe Pietro Innocenti; Vincenzo Vullo; Guido Antonelli; Jason M. Brenchley; Gabriella d’Ettorre; Carolina Scagnolari (Journal of Immunology Research)
Expression of type I and II interferon (IFN) was evaluated in gut-associated lymphoid tissue (GALT) and peripheral blood mononuclear cells (PBMCs) of HIV-1-positive patients on long-term, suppressive, antiretroviral therapy before and after probiotic supplementation. IFNα subtypes and IFNβ were expressed at higher levels in GALT compared to PBMC, whereas an opposite trend of expression was recorded for IFNγ. An increase of IFNα6, IFNα10, IFNα14, IFNα17, and IFNα21 and a decrease of IFNγ were observed in both anatomical sites after probiotic supplementation.